2018
DOI: 10.26552/ems.2018.2.83-95
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Growth and Inequality: Testing Causality and Asymmetries

Abstract: Interest about income distribution and inequality have substantially grown in recent years. First of all, it can be explained by the increase in inequality as a major threat for the stability of society and economy, that often try to associate with the consequences of the globalization process and slowdown in the global economy. Hence the need for research and constructive discussions on inequality, and its causes. As hypotheses, as a rule, statements are tested: economic growth leads first to an increase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The study by Hebbar and Mathew (2017) interprets the significance in harnessing the quality culture of the enterprise to enhance the overall quality of performance. Abakumova and Primierova (2018) and Ahmad et al (2018) support the importance of the quality culture of the enterprise and its consequence of quality performance because, as a rule, households with a high level of earnings prefer high-quality and exclusive goods.…”
Section: Introductionmentioning
confidence: 97%
“…The study by Hebbar and Mathew (2017) interprets the significance in harnessing the quality culture of the enterprise to enhance the overall quality of performance. Abakumova and Primierova (2018) and Ahmad et al (2018) support the importance of the quality culture of the enterprise and its consequence of quality performance because, as a rule, households with a high level of earnings prefer high-quality and exclusive goods.…”
Section: Introductionmentioning
confidence: 97%
“…Enterprises within the same industry have similar legal and financial incentives and consider the behaviour of their competitors when making decisions. Enterprises operating in the same industry consider the performance of their competitors when managing earnings [28,29]. Roychowdhury [30] and Sundvik [31] claim that the industry may have an impact on discretionary accruals and earning management phenomenon, which is also confirmed by the study of Toniato et al [32] which prove the differences in industry characteristics and earnings management behaviour between various economies.…”
Section: Discussionmentioning
confidence: 93%
“…One of the important effects of international sports events is an increase in interest in the country, an increase in indexing in search queries of keywords characterizing the country, improving positions in various ratings and based on indices like for example KOF Globalization Index. Many empirical studies have found confirmation of the relationship between the KOF index and indicators of economic growth, foreign trade, income inequality, etc., including on the basis of data from the Republic of Belarus [17,18].…”
Section: Hypothesis 2: Assessment Of the Impact Of Soft Power Tools Omentioning
confidence: 99%